The contribution of sodium to the bioelectric behaivour of ovarian cancer - McBride, Mark (2021)
Ovarian cancer (OvCa) is the most lethal gynaecological malignancy worldwide and while less prevalent than other malignancies among women, 5-year survival is low and has remained relatively unchanged over the past 40 years. In recent decades the im-portance of bioelectric properties, in particular the plasma membrane potential (Vm),have become increasingly recognised as playing central roles in the regulation of nu-merous biological processes and disease states, including cancer. Recent studies have demonstrated alterations of Vmimpact critical properties of cancer hallmarks, namely sustained proliferation and metastasis. Na+channels play critical roles in regulating Vmand recent evidence has accrued implicating voltage gated Na+channels in metastatic progression of numerous cancers. Limited information however exists for the role of the epithelial Na+channel (ENaC) a constitutively open channel ubiquitously expressed across numerous cell types.